Volatility trading - Sinclair, Euan, 1969- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Popular guide to options pricing and position sizing for quant traders. In this second edition of this bestselling book, Sinclair offers a quantitative model for measuring volatility in order to gain an edge in everyday option trading endeavors. With an accessible, straightforward approach, he guides traders through the basics of option pricing, volatility measurement, hedging, money management, and trade evaluation. This new edition includes new chapters on the dynamics of realized and implied volatilities, trading the variance premium and using options to trade special situations in equity markets. * Filled with volatility models including brand new option trades for quant traders * Options trader Euan Sinclair specializes in the design and implementation of quantitative trading strategies. Volatility Trading, Second Edition + Website outlines strategies for defining a true edge in the market using options to trade volatility profitably.
Option Pricing -- Volatility Measurement -- Stylized Facts about Returns and Volatility -- Volatility Forecasting -- Implied Volatility Dynamics -- Hedging -- Distribution of Hedged Option Positions -- Money Management -- Trade Evaluation -- Psychology -- Generating Returns through Volatility -- The VIX -- Leveraged ETFs -- Life Cycle of a Trade -- Conclusion.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Options (Finance); Hedging (Finance); Futures; Financial futures; BUSINESS & ECONOMICS -- Investments & Securities -- General; Financial futures; Futures; Hedging (Finance); Options (Finance); Electronic books; Electronic books